2007
DOI: 10.1007/s00586-007-0463-2
|View full text |Cite
|
Sign up to set email alerts
|

A biochemical mechanism for resistance of intervertebral discs to metastatic cancer: Fas ligand produced by disc cells induces apoptotic cell death of cancer cells

Abstract: Metastatic spinal cancer is characterized by the maintenance of normal disc structure until the vertebral body is severely destroyed by cancer cells. Anatomic features of the discs have been thought to be the main factor which confer the discs their resistance to metastatic cancer. However, little is known about the biochemical mechanism to prevent or attenuate the local infiltration of cancer cells into the discs. The purpose of this study was to investigate whether Fas ligand (FasL) produced by disc cells ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Interestingly, the cancer cells did not destroy the intervertebral discs even though the whole vertebral body was infiltrated by cancer cells (Figure 2D ). This phenomenon is consistent with the clinical features of spinal tumors in human patients [ 17 , 18 ].…”
Section: Resultssupporting
confidence: 88%
“…Interestingly, the cancer cells did not destroy the intervertebral discs even though the whole vertebral body was infiltrated by cancer cells (Figure 2D ). This phenomenon is consistent with the clinical features of spinal tumors in human patients [ 17 , 18 ].…”
Section: Resultssupporting
confidence: 88%
“…16 The disc also serves as a strong barrier to tumor extension. 1,17 A number of possible explanations for this resistance have been proposed. 9,18,19 The most common one is that the disc is avascular, thus limiting exposure to metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
“… Cornejo et al (2015) have provided evidence that soluble factors derived from notochordal-rich IVD could suppress angiogenesis via inhibiting VEGF signaling pathways, and NC-derived ligands are of significance in targeting neurovascular ingrowth and pain in the degenerative IVD. A previous study has also reported the importance of Fas–FasL (Fas Ligand) interaction, showing that FasL could induce apoptosis of endothelial cells ( Sun et al, 2013b ); besides, FasL generated by IVD could mediate the apoptosis of Fas-bearing cancer cells ( Park et al, 2007 ), and the Fas–FasL network may provide a novel target for the treatment strategies of IDD. These results all suggest that these factors or cytokines might be the molecular monitor for maintaining functions through inducing apoptosis of vascular endothelial cells in addition to the traditional physical barrier.…”
Section: The Relationships Between Ivd Vascularization Inflammation A...mentioning
confidence: 99%